Gender aspects of urban governance in Ukraine’s regions - Мезенцева, Наталія; Кривець, Ольга (Human Geography Journal, 2017)
The article considers the essence of gender equality in urban governance. The analysis of gender ratio in the public service ofUkraineis carried out. It revealed that the highest disparities observed in the western regions, the lowest – in the eastern and southern. Spatial and temporal analysis of gender ratios in urban governance inUkrainein 2009-2015 years is conducted; regional peculiarities of these ratios are identified. The main trends in gender ratios in urban governance inUkraine’s regions are revealed. In particular, the percentage of female mayors inUkraineas a whole tended to reduce; in investigated period,Ukraine’s regions are characterized by different patterns of change in the proportion of female mayors. No female were elected on mayor only in Cherkasy region; after the elections in 2010-2015 women are not elected as mayors in Vinnitsa, Mykolayiv, Sumy and Kherson regions.From 2009 to 2015 regions with the highest share of female mayors is constantly changed, which was due primarily to the electoral preferences of different political forces and, consequently, their nominees for the heads of municipal councils. The most adverse dynamics of gender ratio in the urban governance is observed in Mykolayiv andSumyregions, and the most favorable – in Zaporizhzhya, Dnipropetrovsk, Volyn, Kirovohrad and Ivano-Frankivsk regions. The set of maps reflecting the spatial-temporal variation in gender ratios in urban governance inUkraineis developed.